2016
DOI: 10.1038/srep36128
|View full text |Cite
|
Sign up to set email alerts
|

Linearized texture of three-dimensional extracellular matrix is mandatory for bladder cancer cell invasion

Abstract: In the fields of biomaterials and tissue engineering simulating the native microenvironment is of utmost importance. As a major component of the microenvironment, the extracellular matrix (ECM) contributes to tissue homeostasis, whereas modifications of native features are associated with pathological conditions. Furthermore, three-dimensional (3D) geometry is an important feature of synthetic scaffolds favoring cell stemness, maintenance and differentiation. We analyzed the 3D structure, geometrical measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Ki-67 antigen is a more positive marker of nuclear proliferation, and Ki-67 may be used as a biomarker for determining high risk individuals in pre-cancer population [7][8][9]. Results from Ki-67 antigen assay showed that SBDE significantly decreased the expression of Ki-67 in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 antigen is a more positive marker of nuclear proliferation, and Ki-67 may be used as a biomarker for determining high risk individuals in pre-cancer population [7][8][9]. Results from Ki-67 antigen assay showed that SBDE significantly decreased the expression of Ki-67 in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 antigen is a more positive marker of nuclear proliferation, and Ki-67 may be used as a biomarker for determining high risk individuals in precancer population [7][8][9]. Results from Ki-67 antigen assay showed that PPE significantly decreased the expression of Ki-67 in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 antigen is a more positive marker of nuclear proliferation, and Ki-67 may be used as a biomarker for determining high risk individuals in pre-cancer population [7][8][9]. Results from Ki-67 antigen assay showed that CNCE significantly decreased the expression of Ki-67 in A549 cells.…”
Section: Discussionmentioning
confidence: 99%